2019
DOI: 10.1080/17513758.2019.1593525
|View full text |Cite
|
Sign up to set email alerts
|

Backward bifurcation, oscillations and chaos in an eco-epidemiological model with fear effect

Abstract: This paper considers an eco-epidemiological model with disease in the prey population. The disease in the prey divides the total prey population into two subclasses, susceptible prey and infected prey. The model also incorporates fear of predator that reduces the growth rate of the prey population. Furthermore, fear of predator lowers the activity of the prey population, which reduces the disease transmission. The model is well-posed with bounded solutions. It has an extinction equilibrium, susceptible prey eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 40 publications
(55 reference statements)
0
16
0
1
Order By: Relevance
“…habitat shifts) in order to gain a thorough understanding of how risk effects may cascade through ecosystems (Table 3). Mathematical predictions suggest that risk effects can stabilize prey populations, promote predator–prey coexistence and reduce the spread of disease in prey populations (Sarkar & Khajanchi, 2020; Sha, Samanta, Martcheva, & Chattopadhyay, 2019). Prey with high growth rates may also be less sensitive to risk effects (Sarkar & Khajanchi, 2020).…”
Section: Conclusion and Path Forwardmentioning
confidence: 99%
“…habitat shifts) in order to gain a thorough understanding of how risk effects may cascade through ecosystems (Table 3). Mathematical predictions suggest that risk effects can stabilize prey populations, promote predator–prey coexistence and reduce the spread of disease in prey populations (Sarkar & Khajanchi, 2020; Sha, Samanta, Martcheva, & Chattopadhyay, 2019). Prey with high growth rates may also be less sensitive to risk effects (Sarkar & Khajanchi, 2020).…”
Section: Conclusion and Path Forwardmentioning
confidence: 99%
“…Pal investigated a modified Lesli-Gower eco-epidemiological model with fear effect in prey [47] and observed that an increase in the fear coefficient stabilizes the system dynamics. In [49], Sha et al investigated an ecoepidemiological model with disease in the prey. They assumed that the induced fear also reduces disease transmission along with reproduction and obtained fear-induced backward bifurcation and bi-stability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Model yang diangkat pada artikel ini merupakan gabungan kajian dari model Ekologi dan model Epidemiologi yang disebut dengan model Eko-epidemiologi. Beberapa peneliti telah mempelajari model eko-epidemiologi seperti pada [1,[15][16][17][18][19][20][21]. Artikel ini mempelajari model yang serupa dengan model dalam penelitian Panigoro dkk.…”
Section: Pendahuluanunclassified